CONCEPTUAL PARADIGM OF MUHAMMAD HUSAIN THABATHABA'I’S SYAFA’AT (Tafsir al-Mizan Study on al-Baqarah Verse): PARADIGMA KONSEPTUAL MUHAMMAD HUSAIN THABATHABA’I TENTANG SYAFA’AT (Kajian Tafsir al-Mizan pada Surat al-Baqarah) - Tahir, Muh. Tarmizi; Khaerurrazikin, Khaerurrazikin; Pratama, Oka Putra (Takwil: Journal of Quran and Hadith Studies, 2023)
This research focused on the views and interpretations of Muhammad Husain Thabahaba'i regarding Syafa'at in his commentary, al-Mizan Fi Tafsir al-Qur'an. Discussion of Syafa'at has debating between Sunni and Shi'a groups. One of the debates conveyed in the form of interpretation of the Qur'an or interpretation of the Qur'an. The interpretation of verses regarding Syafa'at was influenced by ideological interests, such as Sunni and Shi'a interests. That is, the Sunni group has a style of interpretation that is different from the Shia group regarding Syafa'at, the giver of Syafa'at, and the form of Syafa'at in the Qur'an. This research departs from anxiety related to differences of opinion regarding Syafa'at from the two groups. In interpreting the verse regarding Syafa'at, the Shi'a group cites some of the narrations of the Shi'a scholars who have an ideology that is contradictory to other Islamic streams, in this case, such as the Sunni sect. This research looked for term on the work of Tafsir al-Mizan Fi Tafsir al-Qur'an. This study used a thematic approach (Maudhu'i) with a descriptive-analytical method. This study found two major conclusions. First, Tabataba'i understood Syafa'at in the sense of obtaining benefits and keeping harm away. Thabathabai divided Syafa'at into two contexts, namely Syafa'at in worldly life, namely an advantage or harm caused by natural causes, such as hunger and thirst, heat or cold, and others and Syafa'at in life in the hereafter, namely the cause of the last thing that will be given by God, such as help, reward, and others. As for the Thabataba'i Syafa'at giving group, they divided it into two types, namely Syafa'at givers in the life of the world and Syafa'at givers in the hereafter. Second, in interpreting QS. al-Baqarah: 48, 123, and 254, Tabataba'i understood it as a rejection of giving Syafa'at absolutely to Jews. Meanwhile, in interpreting QS. al-Baqarah: 255. Tabataba'i was understood that the giver of Syafa'at is absolutely given by Allah SWT and by groups who get permission or are pleased by Allah, such as the Prophet Muhammad SAW and the Shia Imams.